The Age of Communication - Sonja Verwey (Communicare)
In this article the author explores the fundamental shifts that occur in the relationship of the corporation to individuals, and to society as a whole, as a result of the emergence of new information' technology in the Age of Communication. An overview is given of how the new corporate building blocks of connectivity, corporate renewal and culture can evoke and liberate the intellectual capital at the organisation, and more importantly revive the spirit of the organisation. The author concludes that corporations, within the Communication Age, can evolve from dominance to pre-eminence through taking on a broader social role and becoming fundamentally important socio-economic nodes in the individual's everexpanding connectMty networks.